Per- And Poly-Fluoroalkyl Substances (PFAS) Exposure and Risk of Breast, and Female Genital Cancers: A Systematic Review and Meta-Analysis: PFAS Exposure and Risk of Breast and Female Genital Cancers - Seyyedsalehi, Monireh Sadat; Maria Kappil, Elizabeth; Zhang, Sirui; Zheng, Tongzhang; Boffetta, Paolo (La Medicina del Lavoro, 2024)
Background: PFASs, synthetic chemicals, can be encountered by humans through occupational or environmental exposure, and some reports suggest that they can disrupt endocrine and hormonal activities. In this comprehensive review and meta-analysis, we explored the connection between exposure to PFASs and the risks of breast and female genital cancers. Methods: We systematically reviewed the literature from IARC Monographs, ATSDR documents, and PubMed (as of January 2024) for cohort, case-control, and ecological studies on PFAS exposure and breast or female genital cancers. Four reviewers independently screened studies, and data extraction included study design, patient characteristics, and effect size measures. The quality of studies was assessed using the modified version of the Newcastle-Ottawa Scale (NOS). Forest plots of relative risks (RR) were constructed for breast and female genital cancer. Meta-analyses were conducted using random-effects models, stratified analyses, dose-response assessments, and publication bias evaluation. Results: The meta-analysis included 24 studies, comprising 10 cohort, 13 case-control, and one ecological study. The summary relative risk (RR) of breast cancer for PFOA exposure was 1.08 (95% CI = 0.97-1.20; n=21), and for PFOS was 1.00 (95% CI = 0.85-1.18; n=12). The RR for ovarian cancer and PFAS was 1.07 (95% CI = 1.04-1.09; n=12). The stratification by quality score, year of publication, and exposure source did not reveal any differences. However, analysis by geographical region (p=0.01) and study design (p=0.03) did show differences, particularly in terms of incidence. Stratified analyses of the dose-response relationship did not reveal a trend in the risk of breast cancer or female genital cancers, and no publication bias was found for either cancer type. No results were available for cervical and endometrial cancers. Conclusion: In summary, we have found an association between PFAS exposure and ovarian cancer and a possible effect on breast cancer incidence in some specific groups. Although potential bias and confounding prevent conclusions regarding causality, these findings may hold significance for females who encounter such pollutants in their occupational or daily environments.